Jerome Drevon (2024). From Jihad to Politics: How Syrian Jihadis Embraced Politics. Oxford University Press. pp. 261. ISBN 9780197765159 - Mohamed Zacky, Mohamed Fouz (IIUM Press, 2025)
On December 8, 2024, Syrian rebel forces led by Hay’at Tahrir al-Sham (HTS) successfully overthrew former President Bashar al-Assad in a swift military operation. Many had previously thought that the Syrian crisis had subsided, as Assad maintained control over most of the country, except for the north and east, where Sunni rebels and leftist Kurdish groups held power. It was widely believed that Assad had emerged victorious from the civil war and would dictate Syria’s future. Contrary to this prevailing narrative, HTS not only succeeded in ousting Assad and dismantling his security apparatus but also established a de facto government led by Ahmad Al-Sharaa, a former jihadist who transitioned into a statesman. These developments raised a puzzling question: How were the leaders of HTS able to evolve from being jihadist rebel forces to political leaders, and what contributed to this transformation? Drevon’s ‘From Jihad to Politics,’ published just a few months before HTS’s rise to power, explains how and why jihadists transformed into politicians during the Syrian civil war. As such, this book offers revealing insights into the evolution of jihadist movements in the Syrian conflict.